Costs and Benefits of Labour Mobility between the EU and the Eastern Partnership Countries: Country Study on Germany - Costanza Biavaschi; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2013)
Despite the ongoing dialogue on facilitating mobility between the European Union and the Eastern Partnership (EaP) countries, very little is known about the magnitude and characteristics of migrants from these countries. This study aims to fill this gap by studying the size and assimilation patterns of EaP migrants in Germany. Most EaP migrants in Germany come from Ukraine but EaP migrants are a relatively small share of total migrants. EaP migrants experience worse labor market outcomes than other migrant groups, but current and potential migrants hold qualifications in those areas were skill shortages are expected.
Keywords: J15; J26; J61; J62; 330; migration; labour market; assimilation